Financial constraints and corporate governance in family controlled firms in Malaysia - Chu, Ei Yet; Lai, Tian So; Song, Saw Imm (2015)
The hypothesis of financial constraints suggest that firms be denied profitable investment due to inaccessible to external capital markers as debt and equity financing are no longer perfect substitution after firms utilise internal capital. In view of reducing investments during global financial crisis in 2008-2009, the study investigates 157 firms whether they face the issues of financial constraint in Malaysia. In general, non-family firms rely heavily on external debt market while family controlled firms utilising internal cash and reducing their dependence on debt market for their investments. However, the presence of CEO duality does not exaggerate the problem of financial constraints firms, but rather lead family firms to become stagnant in their investments. Independent directors appear to be ineffective in governance family firms for issuing financing for investment. Apparently, their presence in family firms reduce firms’ investment opportunities either through internal cash flow and external debt financing, which could reduce shareholders’ value in long-term.